(untitled) (Research, Society and Development, 2020)
Rapidly developing companies, called Startups, based on technology and innovation, have gained increasing relevance in the business environment in general, mainly because they have great potential to contribute to the growth and economic development of the countries, therefore it is necessary to pay attention to the aspects that involve this organizational model, with regard to its birth, growth, and maturity. In this sense, the so-called innovation ecosystems, seek to bring together all these aspects in a collaborative way, however, what is perceived is that in most cases, in an unplanned way. The objective of this study is to analyze the Bahian Innovation System (SBI), based on measurable parameters integrated with each other, in order to identify the level of development and the quality of their relationships, in order to measure the degree of maturity of the ecosystem. According to ABSTARTUPS (2018), the ecosystem of the city of Salvador is made up of 93 companies and a set of actors involved (government, suppliers, consultants, etc.). For this complete set, 300 questionnaires were sent, involving all the companies and the actors included in the ABSTARTUPS register. Of these questionnaires sent, 80 companies responded (representing 86% of the 93). Of the total of 300 questionnaires sent, 108 questionnaires were answered (representing 36%). From the application of the model by Cukier, Kon and Krueger (2017), to the ecosystem of Salvador, in 2018, it was possible to classify it as a nascent system. In this sense, it is understood that the return of the research was satisfactory for a better understanding of this classification, being possible to verify a low number of active startups and that few of them exceed the level of ideation and validation. There was little participation of researchers in the entrepreneurial movements of the city, since this interaction is indispensable, and actions are needed to encourage greater adherence to the innovation movement.